Validation of the Farsi version of the Suicide Ideation and Behavior Scale - Mehrabi, Ali; Naghavi, Azam; Afsharzada, Mohammad Ershad; Friedrich, Sören; Forkmann, Thomas; Glaesmer, Heide; Teismann, Tobias (Frontiers in Psychiatry, 2023)
Suicide ideation and suicide attempts are prevalent in Farsi speaking populations. The present study aimed at validating the Farsi version of the Suicide Ideation and Behavior Scale (SIBS). Methods: Reliability and validity of the Farsi version of the SIBS were established in a highly burdened Afghan student sample (N = 279). Internal consistency, convergent and discriminant validity were investigated, and confirmatory factor analysis was conducted.The Farsi version of the SIBS was shown to have a unidimensional structure with excellent internal consistency, as well as good convergent and divergent validity.The results suggest that the SIBS is a brief, reliable, and valid measure of current suicidal ideation and behavior that can be used in Farsi speaking populations.